Dry climatic evidence in central Himalaya around 40 ka from lacustrine sediments of Kathmandu Basin, Nepal - Gajurel, AP; France-Lanord, C; Huyghe, P; Mugnier, JL; Sakai, T; Sakai, H; Upreti, BN (Journal of Nepal Geological Society, 2008)
The study area of the research work lies in the Kathmandu Basin. In the northern part of the Kathmandu Basin, delta formed topographic surfaces are exposed. One of the prominent and widely distributed sediments below the surface belongs to the 34 to 50 ka sediments. The sediments are composed of alternating layers of mud, massive to parallel and large-scale cross stratified sands and occasional gravel layers. These sediments can be subdivided into cross– stratified sand beds of delta front facies, black sandy silt of pro-delta facies and parallel or trough cross-stratified gravelly sand of fluvial channel facies. Thickness of the sediment reaches around 40 m. Within the 40 m thick stratigraphy, two widely traceable marker beds in the northern part of the Kathmandu Basin are composed of very thick silt beds and diatomite layer appeared at around 1325 and 1345 m altitudes. The five meters thick marker bed of mud with around one meter thick diatomite layer at an altitude of 1325 m is rich in operculum, gastropods, bivalve and plant fossils. The marker mud with diatomite layer represents the deposit of decantation process in lacustrine environment. Highly enriched C and O isotopes bearing opercula and mollusk shells particularly in the thick diatomaceous beds correspond to around 40 ka carbon-14 age. The ?13C and ?18O isotopic values of operculum vary, respectively, from -4 to 8 ‰ and -2 to 8 ‰ in PDB. The intra-shell ?13C and ?18O values of a gastropod sampled in the diatomaceous layer range from 5 to 8 ‰ and 4 to 8 ‰ in PDB, respectively. In contrast ?13C and ?18O values of modern gastropod shells sampled from artificial pond, paddy field and natural pond in the Kathmandu Valley range, respectively, from -12 to 2 ‰ and -8 to 2 ‰. The rain water samples collected during 2001 to 2002 near the Tribhuvan International airport in Kathmandu show the ?18O values from -16 to 7 ‰ in SMOW. The highly enriched isotopic signatures of around 40 ka sediments in the Kathmandu Basin can be explained by the dry climatic regime in the central Himalaya. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue)p.4